Factors affecting the development of e-government using a citizen-centric approach. Issue 3 (5th October 2015) - Sorn-in, Kanda; Tuamsuk, Kulthida; Chaopanon, Wasu
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to study the factors affecting the development of e-government by using a citizen-centric approach. Design/methodology/approach – This paper is a mixed-methods study consisting of qualitative and quantitative research. Data were collected from government agencies using a structured interview and questionnaire about e-government services. The research was collected from the people responsible for the management of an e-government project in 75 government agencies. In addition, the researcher collected data from 1, 400 citizens by using an e-Survey questionnaire that grouped participants by age. Findings – By using a citizen-centric approach, the paper identified the factors affecting the development of e-government. There were five factors from the viewpoint of government agencies and citizen groups: quality of e-government services, policy and governance, information technology infrastructure, organization and economy and society. Research limitations/implications – The research covered the development patterns of e-government for services from government to citizens only. Practical implications – Seeing the importance of environmental factors for both service providers and service users would facilitate continuous improvement of e-government service provision by government agencies. Social implications – The results reflect citizens' need for e-government services; quality is their priority. Hence, government agencies must consider the quality of the delivery of information and e-government services as they relate to the lifestyles and needs of citizens. Originality/value – The creation of knowledge from merging e-government concepts with citizen-centric principles is a modern government sector management theory. This research stresses the need for the government sector to see the need for e-government and to recognize the factors for its successful development. This means the design and development of e-government services should respond to the increasing needs of the citizens.